If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (3x + 5)(9x + -5) = 0 Reorder the terms: (5 + 3x)(9x + -5) = 0 Reorder the terms: (5 + 3x)(-5 + 9x) = 0 Multiply (5 + 3x) * (-5 + 9x) (5(-5 + 9x) + 3x * (-5 + 9x)) = 0 ((-5 * 5 + 9x * 5) + 3x * (-5 + 9x)) = 0 ((-25 + 45x) + 3x * (-5 + 9x)) = 0 (-25 + 45x + (-5 * 3x + 9x * 3x)) = 0 (-25 + 45x + (-15x + 27x2)) = 0 Combine like terms: 45x + -15x = 30x (-25 + 30x + 27x2) = 0 Solving -25 + 30x + 27x2 = 0 Solving for variable 'x'. Factor a trinomial. (-5 + -3x)(5 + -9x) = 0Subproblem 1
Set the factor '(-5 + -3x)' equal to zero and attempt to solve: Simplifying -5 + -3x = 0 Solving -5 + -3x = 0 Move all terms containing x to the left, all other terms to the right. Add '5' to each side of the equation. -5 + 5 + -3x = 0 + 5 Combine like terms: -5 + 5 = 0 0 + -3x = 0 + 5 -3x = 0 + 5 Combine like terms: 0 + 5 = 5 -3x = 5 Divide each side by '-3'. x = -1.666666667 Simplifying x = -1.666666667Subproblem 2
Set the factor '(5 + -9x)' equal to zero and attempt to solve: Simplifying 5 + -9x = 0 Solving 5 + -9x = 0 Move all terms containing x to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + -9x = 0 + -5 Combine like terms: 5 + -5 = 0 0 + -9x = 0 + -5 -9x = 0 + -5 Combine like terms: 0 + -5 = -5 -9x = -5 Divide each side by '-9'. x = 0.5555555556 Simplifying x = 0.5555555556Solution
x = {-1.666666667, 0.5555555556}
| 2x^2+3x-2x-3=18 | | 11.5(4+X)= | | 5z+5=6-4z+17 | | 6=a+9 | | sec*x-secx-2=0 | | 2(2y+1)=(5y-2) | | 5x+9+4x=9+8+(-7) | | log(9x^3)=2 | | 7a^2-5a-5=-5 | | X^2-25=10 | | 2(25-5)=2(26+5) | | 5x+9+4x=9+8 | | 21/3×5-11 | | 2/7=x/7 | | (X^-3y^3)^-4/(y^3x^-5)^-5 | | 8x^(13/3)-24=0 | | 2*cosx=2*cos*2x | | 12z-4x=-7 | | 10h-10=10-10h | | x^9/2 | | 38x+66=180 | | 3x-(5x)= | | 2n-4=5n+5 | | 80x^2-720=0 | | 8=3x+bx | | 12z+4x=-7 | | 27q-9=180 | | 112x^2-56x=0 | | 2y-7=5-y | | x+.7y=238 | | z=2+3i | | 6n+3+15n+48+3n+10= |